New ACR Recommendations for Treating Juvenile Idiopathic Arthritis - Vinall, Maria (MD Conference Express, 2013)
This article presents a summary of the 2013 update to the 2011 American College of Rheumatology (ACR) treatment recommendations for systemic juvenile idiopathic arthritis (sJIA) [Ringold S et al. Arthritis Rheum 2013]. The purpose of the update was to expand the clinical scenarios for sJIA, to include recent data regarding the efficacy of the interleukin (IL)-1 and IL-6 inhibitors, to include macrophage activation syndrome, and to update the recommendations for follow-up tuberculosis screening for children receiving biologics.